International Bean Rust Nursery: results 1975-1976 - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1979)
The International Bean Rust Nursery (IBRN) is in charge of testing promising bean cv. and breeding lines for resistance to rust (Uromyces phaseoli U. appendiculatus). In 1975, 132 cv. were evaluated at 11 sites in L.A. and the USA; in 1976, 104 cv. were evaluated at 15 sites in Australia, L.A. and the USA. Evaluations were made 30 and 45 days after planting, on the basis of the intensity of infection and the type of pustules. None of the cv. was resistant or immune at all sites, but the introductions Ecuador 299, Mexico 309 and Turrialba 1 were resistant or intermediately so at many of the sites over the 2 yr. Cv. Pinto 650 showed the greatest susceptibility and is therefore considered useful for future studies on rust. (CIAT).